Rethinking the dark side of transnationalism from East Central and Eastern Europe - Grutza, Anna; Kovács, Janka; Pojar, Vojtěch; Schacht, Anastassiya (European review of history, 2024)
Transnational history is an approach that informs global history, although the latter cannot be reduced to the former. Considering the constitutive role of transnationalism in global history, this dossier revisits its categories from East Central and Eastern Europe. Specifically, it builds on and rethinks Kiran Klaus Patel’s and Sven Reichardt’s concept of the ‘dark side of transnationalism’. Crucially, this dossier uses this concept to question the assumption that transnationalism consists of crossing borders and their peaceful unmaking. Instead, it highlights that transnationalism plays a vital role in making new borders and maintaining existing ones. This dossier, therefore, shows that rather than being static, borders can be on the move, and it is often transnational interactions that set them in motion. Through several case studies from the modern history of science and knowledge in this region, the dossier reveals the complex, contingent and fraught nature of transnational exchanges, along with their potential for repression. The experiences of East Central and Eastern Europe thus offer new insights into transnationalism, borders and the reversibility of globalization.
Gesehen am 21.10.2024